Crude Oil and its Economic Effects on Russia - Gryzunov, Anton; Chytilová, Helena; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
With help of regression analysis it was concluded that there is positive relationship between real GDP and Brent oil price. Also the positive dependence was found between real GDP and both index of industrial production and real personal consumption expenditures. On the other hand the relationship between long-term interest rate and real GDP was negative. Unemployment rate and consumer price index were not significant and had negative dependence with real GDP. The aforementioned hypothesis about the negative relationship between GDP and price of oil was confirmed in line with initial theoretical predictions based on detailed review of Russian economy.
Vedoucí práce: Helena Chytilová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses